PENGARUH PEMBERIAN RANGE OF MOTION (ROM) PASIF TERHADAP FLEKSIBILITAS SENDI PADA LANSIA DI PANTI SOSIAL TRESNA WERDA MINAULA KENDARI - Sahmad Sahmad; Reni Yunus; Andi Sarmawan (Jurnal Kesehatan Manarang, 2016)
Aging is a physiological process that will reduce all the functions of organs, one of which is on the musculoskeletal system which can lead to limited motion. This study aimed to determine the effect of Range Of Motion (ROM) of the passive joint flexibility in the elderly in PSTW Minaula Kendari. This research was conducted in PSTW Minaula Kendari. Number of samples 12 people. This study uses the design of one group pretest-posttest. Leverage data is done through observation and documentation. Data were analyzed using paired t-test at 95% confidence level with a = 0.05 using computerized tools (SPSS-20). The results showed that there is the effect of passive ROM tehadap right knee joint flexibility by providing flexion (p = 0.00), extension (p = 0.00), the left knee with the provision of flexion (p = 0.01), extension (p = 0.00), with the provision of the right ankle dorsi flexion (p = 0.00), plantar flexion (p = 0.00), the left ankle with the provision of dorsi flexion (p = 0.00), plantar flexion (p = 0.00), the right foot by giving inverse (p = 0.00), eversion (p = 0.00), the left foot by giving inverse (p = 0.00), eversion (p = 0.00). The conclusion of this study is to show that there is the effect of passive ROM to the flexibility of the joints in the elderly.